BEST PROXIMITY POINT THEOREMS IN NON-ARCHIMEDEAN MENGER PROBABILISTIC SPACES - Karaaslan, Arife Aysun; Karakaya, Vatan (UNIV KRAGUJEVAC, FAC SCIENCE, 2024)
. In this work, we prove best proximity point theorems for 7-contractions with conditions the weak P-property in non-Archimedean Menger probabilistic metric spaces. We give the notion of 7- proximal contractions of first and second type in non-Archimedean Menger probabilistic metric spaces and also we establish best proximity point theorems for these proximal contractions. Lastly, we complete our study by giving examples that support our results.
Keywords: Fixed point; best proximity point; 7-contraction; non-Archimedean Menger probabilistic metric space; NONLINEAR CONTRACTIONS; COMMON; Mathematics